Safety, efficacy, and clinical outcomes of transcatheter tricuspid valve replacement: One-year follow-up - Mao, Yu; Li, Lanlan; Liu, Yang; Zhai, Mengen; Ma, Yanyan; Xu, Chennian; Jin, Ping; Yang, Jian (Frontiers in Cardiovascular Medicine, 2022)
Objective The aim was to evaluate the safety and efficacy of TTVR in patients with severe TR at the 1-year follow-up. Materials and methods This project was a single-center, observational study. From September 2020 to May 2021, 15 patients with severe or extremely severe TR at high risk of traditional surgery were enrolled. All patients had preoperative imaging assessments to evaluate the tricuspid valve and the anatomy of the right heart. All patients were planned to treated with the LuX-Valve (Ningbo Jenscare Biotechnology, Ningbo, China). The LuX-Valve was implanted under the intraoperative guidance of TEE and X-ray fluoroscopy. Data were collected at baseline, before discharge, and at 30 days, 6 months, and 1 year postoperatively. Results The LuX-Valves were successfully implanted in all 15 patients. TR was significantly reduced to ≤ 2 +. One patient died on postoperative day 12 of a pulmonary infection that was considered unrelated to the procedures or the devices. The remaining 14 patients (100.0%) reached the primary end point. One patient (7.1%) was rehospitalized during 1-year follow-up because of device thrombosis. The number of patients who survived at 1 year with New York Heart Association (NYHA) functional class II was higher than that before TTVR (11/14 vs. 0/15, P = 9.11 × 10–4). Patients with peripheral edema and ascites decreased from 100.0 to 46.7% at baseline to 28.6% and 14.3% at 1 year (P = 1.57 × 10–3 and 2.53 × 10–2). Conclusion TTVR is associated with RV remodeling, increased cardiac output, and improvement in NYHA functional class. Using the LuX-Valve for TTVR to treat patients with severe TR is a feasible and relatively safe method with reliable clinical results. Further studies are needed to determine long-term outcomes.